HDAC8 substrates: Histones and beyond1. Issue 2 (22nd November 2012) - Wolfson, Noah A.; Ann Pitcairn, Carol; Fierke, Carol A.; Trievel, Ray
Abstract The lysine deacetylase family of enzymes (HDACs) was first demonstrated to catalyze deacetylation of acetyllysine residues on histones. In subsequent years, HDACs have been shown to recognize a large pool of acetylated nonhistone proteins as substrates. Recently, thousands of acetylated proteins have been discovered, yet in most cases, the HDAC that catalyzes deacetylation in vivo has not been identified. This gap has created the need for better in vivo, in vitro, and in silico approaches for determining HDAC substrates. While HDAC8 is the best kinetically and structurally characterized HDAC, few efficient substrates have yet been substantiated in vivo. In this review, we delineate factors that may be important for determining HDAC8 substrate recognition and catalytic activity, including structure, complex formation, and post‐translational modifications. This summary provides insight into the challenges of identifying in vivo substrates for HDAC8, and provides a good vantage point for understanding the variables important for predicting HDAC substrate recognition. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 112–126, 2013.